The intelligence war against the IRA - Leahy, Thomas (Cambridge University Press, 2020)
"The exposure of two senior republicans as informers for British intelligence in 2005 led to a popular perception that the IRA had 'lost' the intelligence war and was pressurised into peace. In this first in-depth study across the entire conflict, Thomas Leahy re-evaluates the successes and failures of Britain's intelligence activities against the IRA from the use of agents and informers to special-forces, surveillance and electronic intelligence."--